Občanská kompetence učitele a pojetí výuky - Klecandová, Magdalena (Univerzita Karlova, Filozofická fakulta, 2014)
Práce se zabývá občanskou kompetencí učitele a jejím vlivem na pojetí výuky. Ukazuje složky občanské kompetence a představuje ji v osobnosti učitele, ve školských a jiných dokumentech, ve výchově obecně, ve vyučování a v učitelově aktivním přístupu ve škole i v životě. Kvalitativní výzkum zjišťuje vliv občanské kompetence učitele na jeho pojetí výuky. Představuje osobnosti učitelů občanské výchovy a společenských věd, jejich nahlížení na občanskou kompetenci a na její prvky, které pozorují učitelé sami u sebe. Výsledky výzkumu prezentují také celkový přístup k rozvoji této kompetence u žáků a studentů a způsoby podpory dobrého občanství ve výuce. Objevuje se zde i téma apolitičnosti školy. Metodami výzkumu jsou rozhovory s učiteli a pozorování výuky. The thesis follows up citizenship competence of a teacher and its influence on the conception of teaching. It shows components of the citizenship competence and presents it in the personality of the teacher, in educational and other documents, in education generally and in teacher's active approach in school and in life. Qualitative research looks into the influence of citizenship competence of the teacher on his approach to teaching. It introduces the personalities of teachers of civic and social sciences, their views on citizenship competence and its parts, which they observe on themselves. The research results also present an overall approach to developing this competence in pupils and students and ways of promoting good citizenship in school. The topic of an apolitical school also mentioned in the thesis. Interviews with teachers and observations of teaching are used as research methods. Department of Education Katedra pedagogiky Faculty of Arts Filozofická fakulta